1994
DOI: 10.2527/1994.721126x
|View full text |Cite
|
Sign up to set email alerts
|

Apparent digestibility and retention of nutrients bound to phytate complexes as influenced by microbial phytase and feeding regimen in pigs

Abstract: Five barrows of approximately 45 kg BW, fitted with post-valvular T-cecum cannulas at the ileo-cecal junction, were assigned randomly to five treatments (5 x 5 Latin square design) to assess the effect of microbial phytase and feeding regimen (frequency and level) on the apparent digestibilities (total tract [ATTD] and ileal [AID]) and retention of nutrients. A corn-tapioca-soybean meal diet of low intrinsic phytase activity, containing no added inorganic P, was fed either without or with microbial phytase fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

29
130
8
13

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(180 citation statements)
references
References 23 publications
29
130
8
13
Order By: Relevance
“…Growth performance, rib mineralization and P digestibility were all improved when phytase was added to the diet. This is in agreement with studies in the literature which have demonstrated increased daily gains and feed intakes (Beers and Jongbloed, 1992;Jongbloed et al, 1992;Qian, 1996, Yi et al, 1996), increased bone breaking strength or shear force Yi et al, 1996) and increases in P digestibility or retention (Hoppe et al, 1992;Lei et al, 1993a,b;Mroz et al, 1994;Kornegay and Qian, 1996;Yi et al, 1996) when pigs are fed diets supplemented with phytase.…”
Section: Discussionsupporting
confidence: 89%
“…Growth performance, rib mineralization and P digestibility were all improved when phytase was added to the diet. This is in agreement with studies in the literature which have demonstrated increased daily gains and feed intakes (Beers and Jongbloed, 1992;Jongbloed et al, 1992;Qian, 1996, Yi et al, 1996), increased bone breaking strength or shear force Yi et al, 1996) and increases in P digestibility or retention (Hoppe et al, 1992;Lei et al, 1993a,b;Mroz et al, 1994;Kornegay and Qian, 1996;Yi et al, 1996) when pigs are fed diets supplemented with phytase.…”
Section: Discussionsupporting
confidence: 89%
“…De acordo com Wu et al (2006), somente 20 a 50% do total do fósforo dos alimentos de origem vegetal se encontra disponível para aves, pois o restante se encontra na forma de fitato. O fitato, além reduzir a disponibilidade do fósforo, forma complexos insolúveis com as proteínas dietéticas (Ferket, 1993) e com cátions, como cálcio, cobre, zinco, magnésio, manganês e ferro presentes nos alimentos consumidos (Klasing, 1998), que adquirem resistência à digestão enzimática (Mroz et al, 1994), reduzindo a disponibilidade desses nutrientes.…”
Section: Introductionunclassified
“…Dietary microbial phytase supplementation can thus improve phytic-P digestive utilization and consequently reduce P pollution by animal excreta [17,18,23,37,38]. Furthermore, improved nutrient digestibility in animals fed supplemental phytase has been reported in pigs and in poultry [3,4,22,24,25,46,47].…”
Section: Introductionmentioning
confidence: 99%
“…AFP did not have significant effects on the DM and N faecal digestibilities. The effects of AFP on amino acid availability remain to be investigated by measurement of either ileal digestibility [24] or the gastrointestinal absorption of amino acids, in order to overcome the effects of the hindgut microflora on the amino acids availability.…”
Section: Introductionmentioning
confidence: 99%